1989
DOI: 10.5254/1.3536228
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Phenolic Resin Vulcanization of Unsaturated Elastomers

Abstract: It is well known that during the sulfur curing of unsaturated rubbers, two competing reactions occur: (a) crosslinking or vulcanization, and (b) reversion or devulcanization. In the case of butyl rubber, these two competing reactions have been summarized in earlier reports. Tire curing bag (bladder) compounds are usually made of butyl rubber (IIR), a copolymer of isobutene and isoprene, with typically 1–5% of the diene monomer. Curing bags were originally manufactured using sulfur cures. The high temperatures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 0 publications
2
44
0
Order By: Relevance
“…The rubber also acts as a plasticater for the rigid matrix of polypropylene. The torque maxima of rubber loading and the loading/fusion of PP show a decrease with rubber loading and is in accordance to expectation based 14 Schwarz 15 Fitch 16 Lattimer et al 11 Benzyl Cation Giller 20-22…”
Section: Mixing Torque Behavior: Prediction Of the Critical Blend Ratsupporting
confidence: 61%
See 1 more Smart Citation
“…The rubber also acts as a plasticater for the rigid matrix of polypropylene. The torque maxima of rubber loading and the loading/fusion of PP show a decrease with rubber loading and is in accordance to expectation based 14 Schwarz 15 Fitch 16 Lattimer et al 11 Benzyl Cation Giller 20-22…”
Section: Mixing Torque Behavior: Prediction Of the Critical Blend Ratsupporting
confidence: 61%
“…Lattimer et al 11 gives a good survey of results of studies for the resole curing of rubber. They conclude that (i) the cross-links obtained by resole curing consist of bisphenol moieties and (ii) only chroman structures, whereas methylene crosslinks are not demonstrated.…”
Section: Gel Contentmentioning
confidence: 99%
“…Lattimer et al [16] gives a good survey of results of studies for the resole curing of elastomer. The product structures of resole cured elastomers as suggested by Cunneen et al [17], Hultzsch [18,19], Schwarz and Kamenskii [20] are therefore confirmed.…”
Section: Resultsmentioning
confidence: 98%
“…This behavior can be analyzed as a combined effect of both components of the blend. The cross-linked blends showed higher flexural strength and flexural modulus than the Lattimer et al [16] Cunneen [17] Sahwarz [20] Hultzsch [18,19] (Figs. 7 and 8).…”
Section: Flexural Modulus and Crystallization Temperaturementioning
confidence: 89%
“…The (proprietary) EPDM formulation uses a brominated phenolic resin as its curative. Dibenzyl ethers of brominated phenolic resin can be used to increase the crosslink density under normal cure conditions for (KFEPDM) [1][2][3]. However, there is a side reaction (disproportionation) of the phenolic resin that can reduce the crosslink density of the cured polymer and lower its mechanical strength.…”
Section: Introductionmentioning
confidence: 99%